Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
x = 6 and x = -6
Step-by-step explanation:
[tex] \frac{3 - {x}^{2} }{8 + {x}^{2} } = - \frac{3}{4} [/tex]
i) simplify the equation using cross multiplication
[tex]4(3 - {x}^{2} ) = - 3(8 + x {}^{2} )[/tex]
ii) distribute 4 into (3 - x²)
[tex](4 \times 3) + (4 \times ( - x {}^{2} )) = - 3(8 + {x}^{2} )[/tex]
[tex]12 - 4x {}^{2} = - 3(8 + {x}^{2} )[/tex]
iii) distribute -3 into (8 + x²)
[tex]12 - 4 {x}^{2} = ( - 3 \times 8) + ( - 3 \times {x}^{2} )[/tex]
[tex]12 - 4 {x}^{2} = - 24 - 3 {x}^{2} [/tex]
iv) move -3x² to the left-hand side and change its sign
[tex]12 - 4x {}^{2} + 3 {x}^{2} = - 24[/tex]
v) move 12 to the right-hand side and change its sign
[tex] - 4 {x}^{2} + 3 {x}^{2} = - 24 - 12[/tex]
vi) collect like terms
[tex] - x {}^{2} = - 24 - 12[/tex]
vii) calculate the difference
[tex] - x {}^{2} = - 36[/tex]
viii) change the signs on both sides of the equation
[tex] {x}^{2} = 36[/tex]
ix) take the square root to the opposite side of the equation and remember to use both negative and positive roots
[tex]x = + - \sqrt[]{36} [/tex]
[tex]x = + - 6[/tex]
x) write the solutions one with a '+' sign and the other with a '-' sign
[tex]x = 6[/tex]
[tex]x = - 6[/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.